ANALYSIS ON GROUNDWATER WITHDRAWAL AND LAND SUBSIDENCE IN SHANGHAI - Y.-S. Xu; S.-L. Shen; S. Hayashi; Z.-Y. Cai (International Association of Lowland Technology, 2007)
Large-scaled land subsidence due to withdrawal of groundwater in Shanghai was observed. A method based on 3D-groundwater flow model is presented at first to calculate land subsidence in this paper. The model considers the aquitard-aquifer condition of Shanghai soft ground. Based on the proposed groundwater flow model combined with the compressibility of soil layer, subsidence is calculated through unifying in a one model condition. The anisotropic characteristics of soil layer are also considered in the model. The land subsidence, groundwater flow vector, and groundwater drawdown were analyzed using the proposed method. Through comparing between the measured value and calculated value, it indicates that the model simulated the measurement value well. Groundwater flow from west to east at the beginning stage and it flows from east to west after the long-term groundwater withdrawal. Groundwater level is depressed along with groundwater withdrawal.